Spoiled for choice: number of signalers constrains mate choice based on acoustic signals. (27th December 2021) - Tanner, Jessie C; Simmons, Leigh W
Abstract: Animal communication mediates social interactions with important fitness consequences for individuals. Receivers use signals to detect and discriminate among potential mates. Extensive research effort has focused on how receiver behavior imposes selection on signalers and signals. However, animals communicate in socially and physically complex environments with important biotic and abiotic features that are often excluded from controlled laboratory experiments, including noise. "Noise" is any factor that prevents signal detection and discrimination. The noise caused by aggregates of acoustic signalers is a well-known impediment to receivers, but how many individual signalers are required to produce the emergent effects of chorus noise on receiver behavior? In Teleogryllus oceanicus, the Australian field cricket, we assayed female preferences for a temporal property of male advertisement signals, the number of long chirp pulses, using two-, four-, six-, and eight-choice phonotaxis experiments. We found that, as the number of individual signalers increased, receivers became less likely to respond phonotactically and less likely to express their well-documented preference for more long chirp pulses. We found that very few individual signalers can create a sufficiently noisy environment, due either to acoustic interference or choice overload, to substantially impair female preference expression. Our results suggest that receivers may not always be able to express their well-documented mating preferences in nature. Abstract : Animals frequently communicate in large groups, where chorus noise impedes communication. How do individual signals add up to make chorus noise? Using behavioral tests, we found that as few as six male Australian field crickets singing reduced female response rates and prevented mate choice based on songs, due to either acoustic interference or choice overload. In noisy natural environments, selection imposed by receivers on signalers during mate choice is likely weaker than previously thought.